Ogmogaster antarctica (Digenea: Notocotylidae) infecting a dwarf minke whale Balaenoptera acutorostrata (Cetartiodactyla: Balaenopteridae) from the southwestern Atlantic Ocean - Ebert, Mariana Bertholdi [UNESP]; Marigo, Juliana; Guerra Neto, Guilherme; Cremer, Marta Jussara; Silva, Reinaldo Jose da [UNESP] (Springer, 2020)
Digeneans of the genus Ogmogaster Jagerskiold, 1891 are intestinal parasites of whales and pinnipeds. Due to the difficulty in recovering these parasites from opportunistic stranding events of their hosts, very little morphological and molecular data are available on the species of this genus. During a beach monitoring survey on the Southern Brazilian coast, a dwarf minke whale Balaenoptera acutorostrata (Lacepede, 1804) was necropsied and some digeneans were found in its intestine. Morphological and molecular analyses based on the ribosomal DNA SSU and the mitochondrial DNA COI genes were conducted. The morphological data along with the phylogenetic reconstructions allowed the identification of Ogmogaster antarctica Johnston, 1931. This is the first report of O. antarctica infecting a B. acutorostrata in the South Atlantic Ocean. The morphological data, the molecular characterization and the phylogenetic positioning of O. antarctica presented in this study contribute to the knowledge of the helminth diversity of large whales.
Keywords: Notocotylidae; Intestinal parasite; Whale; Molecular characterization; rDNA SSU gene; mtDNA COI gene; Southwestern Atlantic Ocean